KELIMPAHAN DAN KEANEKARAGAMAN FITOPLANKTON DI PERAIRAN PESISIR HOLTEKAMP KOTA JAYAPURA - Leonardo Elisa Aisoi (Jurnal Biosilampari : Jurnal Biologi, 2019)
The research on abundance and diversity of phytoplankton has been conducted in the coastal waters of PLTU Holtekamp, Muara Tami district, Jayapura City, Papua Province. The background of this research is environmental was changed and it caused by human activities, PLTU activities, both of derived from organic and inorganic contamination. The purpose of research was to determine the abundance and diversity of phytoplankton in these waters. This research was observation research, namely by taking samples from 3 stations. Sampling was use planktonnet, observe was use microscope, identified, counted, and analyzed plankton diversity index. Identification was carried out at the Zoology Laboratory of the Biology Education Study Program, Department of Mathematics and Science Education, Teacher and Education Faculty, Cenderawasih University. Plankton abundance was calculated using Lackey Drop Micro Transect Counting Method and Plankton diversity was calculated using formulas Shannon-Weaner. The result shows that there were 17 genera of phytoplankton which were dominated by diatoms and dinoflagellates. The highest abundance found in the station 3 is 2655 ind/l. Diversity index (H') ranged from 1.73 to 1.90 which indicates that there is unstable ecological conditions and dominance index (C) ranging from 0.24 to 0.28 which indicating there no dominant species.